1279. Risk Factors for Colistin Resistance Among Carbapenem-Resistant Klebsiella pneumoniae (CRKP) in a Network of Long-term Acute Care Hospitals (LTACHs). (4th December 2021) - Zhang, Helen L; Han, Jennifer; Lapp, Zena; Snitkin, Evan; Goldstein, Ellie J C; Muldoon, Sean R; Tolomeo, Pam C; Lautenbach, Ebbing
Abstract: Background: Colistin resistance in CRKP presents a serious clinical challenge for patients of LTACHs. However, risk factors for colistin-resistant CRKP have not been previously characterized in this population. Here, we determined risk factors for colistin resistance among CRKP isolates from a network of LTACHs. Methods: CRKP clinical cultures were collected from 21 Kindred Healthcare LTACHs in 4 US states (California, Texas, Florida, Kentucky) from 8/1/14-7/25/15. Cultures collected within 30 days of a prior CRKP culture from the same patient were excluded. Colistin resistance (minimum inhibitory concentration ≥4) was determined using a custom Sensititre TM broth microdilution assay (ThermoFisher Scientific, Waltham, MA). Multivariate logistic regression was performed to evaluate candidate risk factors of age, sex, cirrhosis, chronic kidney disease, culture source, length of stay, indwelling line or tracheostomy, and antibiotic exposure (colistin, fluoroquinolones, 3 rd -5 th generation cephalosporins, piperacillin-tazobactam, carbapenems, and aminoglycosides) for ≥48 hours in the prior 30 days. Results: Among 430 CRKP cultures (237 respiratory, 145 urine, 38 blood, 10 wound) from 375 patients, 144 (33.5%) were colistin-resistant. In multivariate analysis, colistin resistance was associated with prior colistin exposure (odds ratio [OR] = 5.9, 95% CI = 2.5-14.0) and culture source (Wald test for joint significance, p=0.03), with higher odds of colistin resistance among respiratory (OR = 2.9, 95% CI = 1.2-7.2), urine (OR = 1.6, 95% CI = 0.7-4.1), or wound (OR = 2.2, 95% CI = 0.4-11.5) compared to blood cultures. Conclusion: In this sample of CRKP from LTACHs, colistin resistance was associated with prior colistin exposure and respiratory culture source. Other patient factors such as co-morbidities, indwelling devices or tracheostomy, or exposure to other antibiotics/antibiotic classes were not associated with colistin resistance in CRKP. These findings will help inform strategies to reduce colistin resistance and identify LTACH patients at risk of colistin-resistant CRKP. Disclosures: Jennifer Han, MD, MSCE, GlaxoSmithKline (Employee, Shareholder) Ebbing Lautenbach, MD, MPH, MSCE, Merck (Other Financial or Material Support, Member of Data and Safety Monitoring Board (DSMB))